Automata on Series-Parallel Biposets - Ésik, Zoltán; Németh, Zoltán L. (BRICS Report Series, 2001)
We provide the basics of a 2-dimensional theory of automata on series-parallel biposets. We define recognizable, regular and rational sets of series-parallel biposets and study their relationship. Moreover, we relate these classes to languages of series-parallel biposets definable in monadic second-order logic.